Kidney volume and ambulatory blood pressure in children. Issue 5 (16th December 2016) - Gurusinghe, Shari; Palvanov, Arkadiy; Bittman, Mark E.; Singer, Pamela; Frank, Rachel; Chorny, Nataliya; Infante, Lulette; Sethna, Christine B.
Abstract : Low nephron number has been shown to be a risk factor for hypertension (HTN) in adulthood. Kidney volume may serve as a surrogate marker for nephron mass. The relationship between kidney volume and ambulatory blood pressure (BP) in the pediatric population is not known. A retrospective chart review of children younger than 21 years who were evaluated for HTN was performed. Twenty‐four‐hour BP and ultrasonography data were obtained. Multiple regression was used to examine associations between BP and kidney volume. Of 84 children (mean age 13.87 years, 72.6% males), 54 had HTN. Systolic BP index during the awake, sleep, and 24‐hour periods (all P ≤.05) was found to be positively correlated with total kidney volume. Greater total kidney volume was found to be a positive predictor of 24‐hour and sleep systolic index ( P ≤.05). It failed to serve as a predictor of HTN, pre‐HTN, or white‐coat HTN. Contrary to expectation, total kidney volume was positively associated with systolic BP indices.